Corneal Epithelial Removal with a Newly Designed Epithelial Brush - Ho Seok Chung; Seung Hwan Moon; Soon-Suk Kang; Minseop Kim; Hun Lee; Hungwon Tchah; Jae Yong Kim (Journal of Ophthalmology)
This study aimed to evaluate and compare the effectiveness of a newly developed epithelial removal brush with conventional methods in a rabbit model of corneal epithelial defects. The corneal epithelia of thirty-seven rabbits were removed by three different methods including blades (blade group), newly developed epithelial brushes (Ocu group), and conventional rotating brushes (Amo group). The defect area was measured with light microscopy immediately and at 4, 18, 24, and 50 hours after removal. Corneas were obtained immediately and at 24 and 50 hours and subjected to hematoxylin and eosin (H&E) and immunofluorescence staining using proliferating cell nuclear antigen (PCNA) and phosphorylated heat shock protein 27 (pHSP27) antibodies. The residual stromal surface was observed by scanning electron microscopy (SEM). In the Ocu group, epithelia were significantly recovered at 18, 24, and 50 hours compared with immediately after removal, and in the blade and Amo groups, epithelia were significantly recovered only at 50 hours after epithelial removal. The expression levels of PCNA and pHSP27 did not differ among three groups. There was significantly more inflammatory cell infiltration in the blade group than in the other groups. SEM showed a more regular and uniform residual stromal surface in the Ocu group than in the other groups. The newly developed epithelial brush showed better polishing ability and led to earlier significant epithelial recovery and a more regular and uniform stromal surface than conventional methods in this rabbit model of epithelial defects. Accumulation of clinical data is expected to expand the scope of application of new brushes for laser surface ablation.